The role of big data-based precision marketing in firm performance. (3rd August 2022) - Bao, Jiatong; Qu, Yi; Zhao, Shuo; Zheng, Nan
Traditional marketing is faced with the difficulty in adapting to changes. In the new business environment, big data is the cornerstone of future business and precision marketing is the main development direction of future marketing. Mining useful data from large amounts of information and applying it to a company's precision marketing will boost the competitiveness and development of the company. This paper is intended to analyse the influence of precision marketing on the corporations' operating revenue conditions, and it takes Company A Digital Marketing as an example. To achieve this purpose, this study develops definite hypotheses based on the cases and theories of precision marketing and shows precision marketing process including data collection, label analysis, page modification and test results. This study uses decision tree regression analysis using the Python 3.7 and K-means cluster analysis by SPSS 24.0 respectively to test the assumptions. Results are revealed and discussed. Finally in the results, it can be seen that for the high value customer, the time interval from browsing products to purchasing products is short and concentrated within 200 days from the last purchase. In conclusion, precision marketing increases sales and revenue for enterprises.